ANALISIS PENGEMBANGAN DESA WISATA BROMONILAN SEBAGAI DESA WISATA BERKELANJUTAN - Ronny Sugiantoro; Syawal Sudiro; Mecca Adhiendy (Kepariwisataan: Jurnal Ilmiah, 2021)
The bromonilan tourism village is a tourist village that carries the concept of a sustainable tourism village guided by the creation of quality tourism activities. Basically the concept of sustainability through quality tourism seeks to improve the economy and welfare of local communities in particular and tourist satisfaction in general in a sustainable manner. The purpose of this study was to find out how the development of the bromonilan tourism village towards a sustainable tourism village was and what was the right strategy to achieve quality tourism through SWOT analysis. This research was conducted in the first semester of 2021 by implementing a new habit pattern in the village. The research method used is direct observation and through interviews with tourism village managers, as well as local communities. Based on the results of the research that has been carried out, it can be seen that bromonilan has potential natural and human resources to be developed, such as special interest tourism vehicles through outbound and river crossings managed by experts and professionals, Joglo Parisewu as a culinary and photo centers, a unique medical tour through Fish Therapy and also the campground. Access to villages that are easily accessible and close to public facilities is also an advantage of this tourist village. The existence of this extraordinary potential must also be balanced with the participation of all parties, especially by the local community through Pokdarwis to bring up local communities who are empowered in realizing sustainable quality tourism.Keywords: Sustainable Tourism, Quality Tourism, SWOT Analysis